Lifelong learning: a survey on the nursing team necessities - Froes da Silva, Milena; Alves da Conceição, Fabiana; Januário Leite, Maria Madalena (O Mundo da Saúde, 2008)
Lifelong Learning is the essential component of education and development programs for the human resources of institutions. The development of the nursing team is one of the factors that can assure the quality of assistance to the customer and the survival of the institution in this scene of changes and competitiveness. This way, our study made some diagnostics through a survey of the nursing team necessities in Intensive Care Units (ICUs) of a Public Hospital of Metropolitan São Paulo regarding the development of a program of lifelong learning in the institution, as well as the factors that favor and hinder the insertion of assistant nurses of ICUs regarding in loco educative actions and those promoted by the Service of the Hospital’s Lifelong learning.